Study of Complex Formation Between Dicyclohexyl-18- Crown-6 with La3+, UO22+, Ag+ and NH4+ Cations in Acetonitrile-Nitromethane Binary Mixtures - ROUNAGHI, G.H.; HEYDARI, S. (Asian Journal of Chemistry, 2010)
The complexation processes of La3+, UO22+, Ag+ and NH4+ cations with macrocyclic ligand, dicyclohexyl-18-crown-6 (DCH18C6) was studied in acetonitrile-nitromethane binary solutions at different temperatures using the conductometric method. The conductance data show that with the exception of complexation of NH4+ cation with this macrocyclic ligand, the stoichiometry of all the complexes which are formed in solutions, is 1:1 [M:L]. A different behaviour was observed in the case of complexation of NH4+ with DCH18C6 in which a 1:2 [M:L2] complex is formed in solutions. A non-linear behaviour was observed for changes of log Kf of (DCH18C6.La)3+, (DCH18C6.UO2)2+ and (DCH18C6.Ag)+ complexes versus the composition of the binary mixed solvents. This behaviour may be related to hetero selective solvation of the cations and the ligand and also solvent-solvent interactions in these binary mixed solvent systems. The values of thermodynamic quantities (ΔHºc, ΔSºc) for formation of the complexes were obtained from temperature dependence of their stability constants using the van’t Hoff plots. The results show that in all solvent systems, positive values of ΔSºc characterize the formation of the complexes. The selectivity order of the ligand for the studied cations in pure acetonitrile and acetonitrile-nitromethane binary solutions (mol % AN = 50.0 and 75.0) was found to be La3+ > UO22+ > Ag+.